Encouraging Environmental Sustainability in University Campuses: Evidence from Türkiye - Erkin Sarı; Bengi Öner-Özkan (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
The primary aim of the current study is to comprehend the development and evolution of environmental attitudes and to examine on-campus pro-environmental engagement among 16 undergraduates from two public Turkish universities through semi-structured interviews. Our qualitative analysis highlighted that several factors (e.g., the existence of environmentally aware role models in elementary education) are responsible for the formation of respondents’ environmental attitudes. The current paper also points out that litter pollution is a major problem on university campuses. To combat this problem, most respondents in the study reported taking proactive measures (e.g., disposing of the waste properly) to reduce littering and promote sustainable practices. In addition to fighting against littering, they actively take part in pro-environmental activities (e.g., tree plantation), prefer ecologically friendly mobility options (e.g., biking, using shuttles), financially support ecological organizations and attending their activities, and conserve energy. They also reported several factors for motivating (e.g., the willingness to protect the campus ecosystem) and hindering (e.g., lack of time) their on-campus pro-environmental engagement. Furthermore, our respondents pointed out that all stakeholders (e.g., rectorate, employees, students) regarding campus sustainability should take part (e.g., using effective measures for rewarding and penalizing) in amplifying the effectiveness of on-campus pro-environmental behaviors. With these findings, the current paper made important theoretical and practical contributions to campus sustainability.